Promoting Fave Hotel’s Rungkut Meeting Rooms and Rooms Using a Marketing Booklet - Alexandra Ricci Pradnya Paramita (Institute of Research and Community Outreach - Petra Christian University, 2019)
Fave Hotel Rungkut is a 3 – star hotel, located in Jl. Kaliraya Rungkut No. 23 – 25. Fave Hotel Rungkut has 175 total rooms with 169 standar rooms and 6 suite rooms. They also offer 4 medium and 2 large meeting rooms. Their main competitors are Cleo Business Hotel, Zest Hotel Jemursari, and Amaris Magarejo. The main problem that Fave Hotel Rungkut is facing is the decline of upselling rooms and meeting rooms in September – November 2018. To solve the problem, I made a marketing booklet to help sales team sell the products of Fave Hotel Rungkut. A marketing booklet is made in English and Indonesia in order to make their local and foreign customers understand. This marketing booklet will be useful and helpful for sales and marketing team to promote or show their products to their target market. Keywords: Promotion, Hotel, Marketing Booklet